2011
DOI: 10.1186/1471-2288-11-16
|View full text |Cite
|
Sign up to set email alerts
|

A clinical trial alert tool to recruit large patient samples and assess selection bias in general practice research

Abstract: BackgroundMany research projects in general practice face problems when recruiting patients, often resulting in low recruitment rates and an unknown selection bias, thus limiting their value for health services research. The objective of the study is to evaluate the recruitment performance of the practice staff in 25 participating general practices when using a clinical trial alert (CTA) tool.MethodsThe CTA tool was developed for an osteoporosis survey of patients at risk for osteoporosis and fractures. The to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
0
22
1
Order By: Relevance
“…99% of the subjects randomized were recruited by the lead, committed PI at each participating institution who presented the trial as a treatment option to potential subjects on the day when the biopsy diagnosis was given to the patient. Although previous studies have reported the significant on enrollment impact of individual physicians of patients into clinical trials [2425] we observed a significant impact, with the majority of subjects recruited using this strategy, higher than most reported studies. We attribute the success of this recruitment strategy to several factors: (a) committed and experienced physicians; (b) participation of physicians in the design of this clinical trial; (c) patient's high level of trust in their physician; (d) timing of presentation of the trial as an option, post biopsy, and; (e) absence of treatment options for men at high risk for prostate cancer other than surveillance.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…99% of the subjects randomized were recruited by the lead, committed PI at each participating institution who presented the trial as a treatment option to potential subjects on the day when the biopsy diagnosis was given to the patient. Although previous studies have reported the significant on enrollment impact of individual physicians of patients into clinical trials [2425] we observed a significant impact, with the majority of subjects recruited using this strategy, higher than most reported studies. We attribute the success of this recruitment strategy to several factors: (a) committed and experienced physicians; (b) participation of physicians in the design of this clinical trial; (c) patient's high level of trust in their physician; (d) timing of presentation of the trial as an option, post biopsy, and; (e) absence of treatment options for men at high risk for prostate cancer other than surveillance.…”
Section: Discussioncontrasting
confidence: 83%
“…We attribute the success of this recruitment strategy to several factors: (a) committed and experienced physicians; (b) participation of physicians in the design of this clinical trial; (c) patient's high level of trust in their physician; (d) timing of presentation of the trial as an option, post biopsy, and; (e) absence of treatment options for men at high risk for prostate cancer other than surveillance. Additionally, these recruitment rates were accomplished by the MD without any clinical trial alert system or an electronic medical system [17,25] to assist the physicians with this process at each of these sites, emphasizing the commitment and the feasibility of physicians to recruit high risk subjects in chemoprevention trials. Further research is recommended to more clearly elucidate approaches critical for successful physician involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic pop‐ups in the GP clinical information system were not popular with healthcare professionals in this study but along with GP identification were responsible for the identification of 13 patients leading to one recruited. Pop‐ups have been shown in other studies to have the potential to easily identify large numbers of suitable patients.…”
Section: Discussionmentioning
confidence: 99%
“…Documentation of how new digital tools for clinical trials have been developed is scarce [11,12], but recent evaluations of some digital tools are available [13-15]. During the 2nd Clinical Trials Methodology Conference in 2013, McPherson et al discussed whether to use a commercial system or build one’s own software for use in clinical trials [16].…”
Section: Introductionmentioning
confidence: 99%